Sorghum protein ingredients: Production, compositional variability and enhancement of aqueous dispersibility through homogenization - Gallo, Thais Cristina Benatti [UNESP]; Beaumal, Valérie; Houinsou-Houssou, Bérénice; Viau, Michèle; Ribourg-Birault, Lucie; Sotin, Hélène; Bonicel, Joëlle; Boire, Adeline; Queiroz, Valéria Aparecida Vieira; Mameri, Hamza; Guyot, Sylvain; Riaublanc, Alain; et al. (Elsevier, 2024)
Sorghum protein ingredients show promising applications, given that sorghum is a resilient grain with high protein content and bioactive components, such as tannins, in certain genotypes. This study aimed to investigate the production and characterization of sorghum protein ingredients extracted from both tannin-free and tannin-rich cultivars, along with an examination of their behavior in aqueous suspensions. The use of high-pressure homogenization to improve ingredient dispersibility was also assessed. Protein extracts exhibited protein contents ranging from 50 to 67 g/100 g (wet basis), with the highest values obtained in tannin-free samples. Total lipid contents were between 18 and 26 g/100 g (wet basis), with a high contribution of free fatty acids (68–76 g/100 g lipids), and tocopherol contents ranged from 1080 to 2039 µg/g total lipids. This is substantially higher than the lipid content in flours, implying an accumulation of lipids during the protein extraction process. While the dispersibility of the protein extracts in aqueous media was initially limited, high-pressure homogenization proved effective in reducing the average size of the particles in suspension, from 9–66 µm to 1.8–2.5 µm. This processing step significantly enhanced protein dispersibility by up to 288 %, especially for the tannin-rich samples.
Keywords: Composition; Kafirin; Particle size; Solubility; Sorghum lipids; Tannins